ASTROLOGY APPLICATIONS USING PSYCHOLOGY AND VISUAL YADA 6.0 PROGRAMMING LANGUAGE - Fetria Krisna Agustina; Haryanto, SKom, MMSI Haryanto, SKom, MMSI (Jurnal Sistem Informasi, 2003)
Writing is about the problems that predict about astrology and psychology. Among others, made an application in predicting the activities in search of a use of personal information. This application can be used to create an information in the search for personal characteristics about the data's personality and needs.This application is created using Visual Basic 6.0 has a graphical interface of Windows that is easy to use and simple user.